INFECTIOUS COMPLICATIONS IN PATIENTS UNDERGOING ORTHOTOPIC HEART TRANSPLANTATION - Y. P. Ostrovsky; L. V. Ratiok; I. A. Hrabianiuk; O. A. Yudina; E. K. Kurlyanskaya; M. G. Kolyadko; V. S. Tihomirov; T. A. Dubovik; V. S. Khudnitskaya (Вестник трансплантологии и искусственных органов)
This article presents a retrospective analysis of infectious complications in the structure of morbidity and mortality of the patients underwent orthotopic heart transplantation. A significant role was assigned to the predisposing to in- fection factors. This study was based on the two years heart transplantation experience in the Republic of Belarus.